The impact of negative e-WOM on consumers’ purchase intention: The Malaysian context - Haque, A. K. M. Ahasanul; Rahman, Moshiur Mohammad; Kabir, SMH; Abdullah, Shakif (2019)
The impact of negative eWOM about certain products on consumers is remarkable. This research is aiming to answer the impact of negative eWOM whether negative eWOM has any specific motives and how it effects over consumers’ purchase intention. A quantitative approach will be employed while questionnaire data will be collected from more than 250 Malaysian consumers and test empirically a model that incorporates both motives of negative eWOM towards impact on purchase intention. Structural equation modelling will be used to test the research hypotheses. The findings will also show the different forms of negative word-of-mouth behaviors which will be labelled advice seeking, dissonance reduction and altruism while venting negative feelings proved to be ineffective motive. However, it will show how each of these behaviors varies in terms of the target consumers towards the motivational analysis. The result will be able to confirm that negative eWOM motives the consumers and have a significant impact on purchase intention. This will contribute insights into the neglected area of consumers negative word-of mouth and argues for identification in the forms of consumers which is an important step towards consumers purchase intention. While in the article, a series of propositions will develop which future researchers may find useful in advancing research in this area.